The Economic Growth Catalyzers at the European Level, in the Context of the 2008 Financial Crisis - Dan Costin Nițescu; Valentin Murgu (Amfiteatru Economic)
The research addresses the issue of identifying new catalysts for economic growth at European level, supporting the future mix of policies. It was analyzed, the nature of the intercorrelation between the economic indicators Gross Domestic Product (GDP and GDP per capita), conventionally assimilated to economic growth and relevant macroeconomic indicators, interacting in a complex manner (domestic credit, export of goods and services, Foreign Direct Investment ‒ net inflows, saving). In the first two parts of this paper we present the main challenges and macroeconomic evolutions at the European level, as well as, relevant aspects reflected in researches and representative studies for the issues addressed; the third part of the article includes the empirical study for 20 European countries over a period of 17 years, where, based on the use of the multiple regression model, we analyzed the correlations between the indicators for the Gross Domestic Product ‒ endogenous variables and the main macroeconomic country indicators ‒ exogenous variables (domestic credit, export of goods and services, Foreign Direct Investment ‒ net inflows, savings). Part four highlights the results of the research alongside other issues relevant to future analysis. The research reflects the evolution of economic growth, measured both by the change in GDP and by the change in GDP per capita that can be explained mainly for the data panel considered in the analysis, by means of two catalytic factors: the dynamics of the domestic credit, respectively that of the savings, variables with a lower degree of volatility